The early and mid-term outcomes of acute type A aortic dissection patients with ECMO - Meng, Qingqing; Jiang, Hongkai; Li, Tianbao; Pang, Shanwen; Zhou, Chengbin; Huang, Huanlei; Sun, Tucheng; Wu, Jinlin (Frontiers in Cardiovascular Medicine, 2024)
BackgroundAcute type A aortic dissection (ATAAD) poses significant challenges in cardiovascular management due to its high morbidity and mortality rates. Postcardiotomy cardiogenic shock (PCS) is a severe complication following ATAAD repair that complicates postoperative recovery. Extracorporeal membrane oxygenation (ECMO) has emerged as a potential life-saving intervention in this context, yet the specific outcomes related to ECMO in ATAAD patients remain insufficiently studied.MethodsThis retrospective single-center study reviewed the medical records of 479 patients who underwent ATAAD surgery from September 2017 to June 2021. Patients were stratified into those requiring postoperative ECMO support and those who did not. Data collected included demographics, operative details, and postoperative outcomes.ResultsOf the cohort, 19 patients (4.0%) required ECMO support. The ECMO group exhibited significantly higher mortality rates (57.9% vs. 5.4%, p < 0.001) and increased complications, including a higher rate of continuous renal replacement therapy (84.2% vs. 24.3%, p < 0.001) and prolonged ICU stays (14.5 days vs. 7.6 days, p = 0.009). Survival analysis demonstrated a stark contrast in 3-year survival rates, with 36.8% for the ECMO group vs. 92.8% for non-ECMO patients (p < 0.001).ConclusionsECMO can be a crucial intervention for ATAAD patients suffering from PCS; however, it is associated with significantly higher mortality and complications. Despite lower long-term survival rates compared to non-ECMO patients, ECMO may offer a survival benefit as a salvage therapy. Interpretation is limited by the retrospective single-center design, small ECMO cohort size, and lack of post-discharge quality-of-life data.